Effect of Nitrogen (N) and Potassium (K) on Growth and Yield of Onion - Ahmed, Tarik; Paul, Alok Kumar; Ali Mollick, Md. Omar; Sumon, Munshi Mohammad; Haque, Md. Imdadul (International Journal of Bio-resource and Stress Management, 2023)
The experiment was conducted at the Research Farm of Sher-e-Bangla Agricultural University, Dhaka-1207, Bangladesh in rabi season during December 2019 to March 2020 to investigate the effect of nitrogen (N) and potassium (K) on growth and yield and find out the optimum dose of N and K for maximum yield of onion. The experiment consists of 8 treatments as Control (no nitrogen+no potassium); Nitrogen @ 80 kg ha-1+Potassium@ 80 kg ha-1; Nitrogen @ 100 kg ha-1+Potassium @ 80 kg ha-1; Nitrogen @ 100 kg ha-1+Potassium @ 100 kg ha-1; Nitrogen @ 120 kg ha-1+Potassium @ 100 kg ha-1; Nitrogen @ 120 kg ha-1+Potassium@ 120 kg ha-1; Nitrogen @ 140 kg ha-1+Potassium @ 100 kg ha-1; Nitrogen @ 140 kg ha-1+Potassium @ 120 kg ha-1. Recommended dose of phosphorus, sulphur, zinc and boron were used in this experiment. The experiment was laid out in a randomized complete block design (RCBD) with three replications. The tested variety was BARI Piaz-4. Data were collected on different yield attributes, growth and quality of onion and postharvest soil analysis. Results of the experiment revealed that N and K significantly (p<0.05) influenced plant height, leaves plant-1, leaf length, dry matter content of leaves, diameter of bulb, length of bulb, fresh weight of bulb plant-1, dry matter content of bulb plant-1, bulb yield, total nitrogen (%), available phosphorus (ppm), exchangeable potassium (meq 100 g-1). Results suggested that nitrogen (N) and potassium (K) application had significant positive effect on plant and soil.